The Influence of Organizational Commitment, Team Cohesion, and Leadership Style on Employee Retention in the Hotel Industry - Lisa Andriani; Rizky, Gia (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This research aims to analyze the influence of organizational commitment, team cohesion, and leadership style on employee retention in the hotel industry in the Special Region of Yogyakarta. This research used a simple random sampling technique with a total of 153 respondents. Primary data collection was carried out using a questionnaire method via Google Form which had been tested for validity and reliability. The analysis used in this research is logistic regression analysis with the help of the IBM SPSS statistics 25 program. The results of data analysis show that simultaneously the factors of organizational commitment, team cohesion and leadership style have a positive and significant effect on employee retention. Partially, organizational commitment and team cohesion have no effect on employee retention. However, leadership style has a positive and significant effect on employee retention.